Introduction to Japanese Finance: Markets, Institutions, and Firms - Higgins, Robert C. (Journal of Financial and Quantitative Analysis, 1985)
Changes in the Japanese financial system over the coming decade will play a significant role in the functioning of U.S. financial markets and, indeed, of the entire U.S. economy. From World War II through at least the mid–1970s, the United States was a major exporter of investment capital in the form of foreign direct and portfolio investment. More recently, low U.S. savings rates, recurring federal budget deficits, reduced sovereign lending by U.S. banks, and, possibly, high real returns on domestic investment have combined to make the United States a major importer of capital. At the same time, large trade surpluses and very high savings rates in Japan have more than offset increases in government borrowing to make Japan the world's principal capital exporter, a position it is likely to hold for some time. These are fundamental changes.